KONSEP PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DI SD IT PERMATA HATI PALEMBANG - Fitria Hardiyanti; Medeawati; Siti Komariah; Ela Nadia; Sari; Ami Latifah (UNISAN JURNAL, 2023)
This exploration means to portray the idea of Islamic strict training learning at Permata Hati Primary School, Palembang. This examination utilizes a subjective clear methodology with library research techniques. The consequences of the exploration demonstrate the way that the instructive strategies that can be applied allude to the Al-Quran technique, specifically the amstal strategy, qishah strategy, ibrah mauidzah technique, hiwar jadali strategy, uswah hasanah technique, and targhib tarhib technique. In the mean time, assessment applied in Islamic schooling isn't simply surveying a movement precipitously and as it turns out, yet is an action of evaluating something in an arranged, precise way, in light of clear and thorough goals that cover all viewpoints, both from a mental, full of feeling and psychomotor point of view. point of view. , and assessment of Islamic strict instruction learning can be done verbally or non-verbally, composed or unwritten, which plans to quantify scholarly ability, social skill, social capability and profound skill.